EFEKTIVITAS MEDIA APLIKASI ABATA HIJAIYAH PADA ANDROID DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH BAGI ANAK TUNARUNGU (SINGLE SUBJECT RESEARCH DI KELAS I SLBN CENTER PAYAKUMBUH) - Nofira Fadhillah, Elsa Efrina, Mega Iswari (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the problems that researchers in the field discovered that the deaf child in the class I SLBN Center Payakumbuh. Children new to two hijaiyah, namely alif and ba. When compared with the others, has mastered ten hijaiyah, both to show and express the hijaiyah. This research uses experiment approach in the form of single subject research (study a single subject), using the design of A-B-A, and data analysis techniques using visual analysis chart. The research Subjects were deaf child. Assessment in this study is to measure the percentage of students' abilities to demonstrate and speaks eight hijaiyah. Based on the results of this study shows that the ability of deaf child to recognize letters hijaiyah can be enhanced through the application of media Abata hijaiyah on android. In the baseline condition (A1) conducted four times a meeting, children can not pronounce the letter hijayah show and given that the percentage is 0% at the first meeting until the fourth meeting. In the intervention condition (B) performed 10 times and the ability of deaf child meetings increased from five to meeting up to fourteen with the highest score of 100% to indicate or say, while in the baseline condition (A2) held six meetings and the child's score 100% is the highest for the show also speaks eight hijaiyah. If seen from the analysis of the data can be explained that the change of tendency toward increased (+) from baseline to the intervention condition or intervention to the baseline 2. Small percentage of data that describe the overlap effect by using the media intervention, the better the ability to recognize letters hijaiyah deaf child. Thus the hypothesis (Ha) proposed is acceptable. It means that the media application on android Abata hijaiyah effective for improving cognitive ability in children with hearing hijaiyah Payakumbuh SLBN Center. It can be concluded that the media application on android Abata hijaiyah effective for improving cognitive ability in deaf child hijaiyah.